Introducción a las plantas endémicas del Perú - León, Blanca (2006)
Endemism is an important means to evaluate biological conservation goals and strategies. In this book we used the concept of national endemism. We examined different taxonomic levels, including genera, species and sub specific categories. For evaluating the degree of risk, we used herbaria specimens as representing samples of populations. Forty-three people participated between 2003 and 2005. Similar to other tropical floras of western South American, Peru's endemics are linked to the presence of the Andes. We recognize a total of 5509 endemic taxa, representing 27.9% of the total flora. We applied IUCN, version 3.1, criteria and categories to 76% of the endemic flora. The most at risk correspond to Endangered (33%), Critical Endangered (18%) and Vulnerable (10%). The departments with the highest number of endemic taxa are found among those with Andean slopes, and wide altitudinal and ecological features, similar to Peru's overall floristic trends. We hope that this book of Peru's will open the doors for monitoring and protection of Peru's endemic flora.